Sistem sokongan keputusan cerdas untuk penilaian keteknousahawanan - Ahmad Nazri, Mohd. Zakree (2001)
The purpose of h s study was to model, design and develop an intelligent decision support system, which is capable of identifying the characteristics of a high information technology venture at each stage of its growth. This system focuses on serving venture capitalists in the process of eduation and selection in efficient and effective approach. Early findings in this study conclude that venture capitalists barely rely on their instincts during the decision making process. Researcher scientifically has proven that this method has a number of critical drawbacks. By using a framework developed by Keen, Morton and Meador and the Bell-Mason model, the Multi Attribute Analysis and an Inference engine were integrated into the system. The system named Technopreneurial Intelligent Decision Support System (TDSS) was developed using Visual Basic 6.0, Prolog and Knowledge Specification Language. From this study, it is concluded that TIDSS can ease the evaluation and selection process. This study also has derived a systematic approach m evaluating technopreneur by improving the process effectiveness and proficiency. TIDSS is also capable in training new user with the knowledge based system as it contains technical articles and help file in understanding Bell-Mason model.